GAMBARAN PELAKSANAAN KEBIJAKAN PEMBATASAN PERJALANAN DOMESTIK DALAM UPAYA PENANGGULANGAN COVID-19 TAHUN 2020 OLEH KKP TANJUNG PRIOK - GITA CHANDRA (Yayasan Pendidikan Medika Indonesia, 2021)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) as a Public Health Emergency of International Concern (PHEIC) on March 11 2020 Covid-19 was declared by WHO as a pandemic. Technological advances can also affect the pattern of disease spread. The current speed of transportation allows travelers to move from one country to another with a travel time that is shorter than the incubation period. Tanjung Priok Port is one of the export-import gateways in Indonesia, so it has the potential to be the entry and exit point for infectious diseases. The Tanjung Priok Class I KKP which is located at the Tanjung Priok port has the main task and function of preventing the entry and exit of infectious diseases that have the potential to become PHEIC. In January to December 2020, the number of domestic sea transportation passengers in Indonesia amounted to 14.2 million, a decrease of 40.66 percent compared to the same period 2019. For Tanjung Priok Port, it was 76.51 percent of the total passengers, namely 1,086,442 passengers. This research is an analysis of policy implementation research using qualitative methods by observing then researchers continue with in-depth interviews to see an overview of the implementation of domestic travel restriction policies in the effort to overcome Covid-19 by KKP Class I Tanjung Priok. The results of this study are less effective because many changes occur in a short time. Existing policies need to be monitored and evaluated on the implementation of a policy so that it can be ascertained whether it is running as it should